The Roles of Genetic and Early-Life Environmental Factors in the Association Between Overweight or Obesity and Hypertension: A Population-Based Twin Study - Xi, Yu’e; Gao, Wenjing; Zheng, Ke; Lv, Jun; Yu, Canqing; Wang, Shengfeng; Huang, Tao; Sun, Dianjianyi; Liao, Chunxiao; Pang, Yuanjie; Pang, Zengchang; Yu, Min; et al. (Frontiers in Endocrinology, 2021)
Aims/hypothesis We aimed to explore whether and to what extent overweight or obesity increases the risk of hypertension, and further to estimate the roles of genetic and early-life familial environmental factors in their association. Methods This prospective twin study was based on the Chinese National Twin Registry (CNTR), which collected information from self-report questionnaires. We conducted unmatched case-control analysis to examine the association between overweight or obesity and hypertension. And further to explore whether genetics and familiar environments shared within a twin pair, accounted for their association via co-twin matched case-control design. Generalized estimating equation (GEE) models and conditional logistic regressions were used in the unmatched and matched analyses, respectively. Then, we used logistic regressions to test the difference in odds ratios (ORs) between the unmatched and matched analyses. Finally, through bivariate twin model, the roles of genetic and environmental factors in the body mass index (BMI)- hypertension association were estimated. Results Overall, we included a total of 30,617 twin individuals, of which 7533 (24.6%) twin participants were overweight or obesity and 757 (2.5%) developed hypertension during a median follow-up time of 4.4 years. In the GEE model, overweight or obesity was associated with a 94% increased risk of hypertension (OR=1.94, 95% confidence interval (CI): 1.64~2.30). In the conditional logistic regression, the multi-adjusted OR was 1.80 (95% CI: 1.18~2.74). The difference in OR between unmatched and matched analyses was significant (P=0.016). Specifically, overweight or obesity was not associated with hypertension risk in the co-twin design when we full controlled genetic and familiar environmental factors (OR=0.85, 95 CI: 0.46~1.59). After controlling for age and sex, we found the positive BMI-hypertension association was mainly explained by a genetic correlation between them (rA= 0.59, 95% CI: 0.44~1.00). Conclusions/interpretation Genetics and early-life environments shared by participants within a twin pair appear to account for the association between overweight or obesity and hypertension risk.